Intergalactic γ-ray propagation: basic ideas, processes, and constraints. (February 2019) - Dzhatdoev, Timur; Khalikov, Emil; Podlesnyi, Egor; Telegina, Anastasia
Abstract: We review extragalactic γ-ray propagation models with emphasis on the electromagnetic (EM) cascade process in the magnetized expanding Universe. We consider cascades initiated by primary protons of ultra-high energy accelerated by blazars and show that the observable spectrum is similar to the universal spectrum of a purely EM cascade. We also present a detailed calculation of the observable angular distribution for the case of EM cascades developing from relatively nearby ( < 20 Mpc) sources. Finally, we calculate the point-like source differential sensitivity of a novel liquid Argon time projection chamber γ-ray telescope and show that its sensitivity is several times better than the Fermi LAT sensitivity in the 100 MeV – 100 GeV energy range.